Prevention of Subsequent Hip Fractures among Geriatric Population with Use of Bisphosphonates. - Shah , Syed Kamran Ali; Ghazi , Muhmmad Arsalan; `Muhammad Sufyan; Muhammad Mustafa; Najjad , Kazim Rahim; Peracha , Asif (International Journal of Endorsing Health Science Research, 2022)
Background: In the geriatric population, osteoporotic or fragility hip fractures hold a significant health burden and are scrupulously linked with a greater possibility of morbidity and mortality among this population group, even though there is an increased incidence of subsequent hip fractures. Bisphosphonates are extensively used in treating and preventing fragility hip fractures as prophetically. Methodology: From March 2014 to February 2020, a total of 2430 patients were enrolled with their first hip fracture. After determining the second hip fracture, a comparison between non-compliant and compliant bisphosphonate users (Ibandronic Acid) was conducted. Medication Possession Ratio of more than 80% post first hip fracture treatment was defined as bisphosphonates compliant user. Results: Among 2430 patients, 65.2 years was the mean age at the first hip fracture (ranging from 51 to 91 years). A total of 146 (6.0%) patients suffered from second hip fractures at a mean duration of 29.45 months post first hip fracture. 2nd hip fracture was observed in only 3.5% (30/860) of compliant bisphosphonate users compared to non-compliant users with 7.4% (116/1570). Conclusion: Among the geriatric population, the use of bisphosphonate (Ibandronic Acid) has a significant impact on preventing subsequent hip fractures. Hence this emphasizes the need to use bisphosphonates in clinical practice to help to minimize the burden of hip fractures.